Rola państwa w stymulowaniu zrównoważonego rozwoju rolnictwa i obszarów wiejskich - Przygodzka, Renata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The purpose of the article is to present the role of the state in supporting sustainable development of agriculture and rural areas. The state's activity in this field is forced by the occurrence of external effects generated by business activities conducted in rural areas (especially agriculture). An example of the most advanced policy of supporting balanced development of agriculture and rural areas is the policy (currently more rural than agricultural) of the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 27-33